PEMANFAATAN MEDIA SOSIAL DALAM PROMOSI KUE BROWNIES - Yuliza, Mai; Yurasti; Putra, Endang Tirtana; Puta, Eko; Mardahleni (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
This Community Service (PM) activity aims to improve the skills of small entrepreneurs (SMEs) in Kinali District, West Pasaman Regency, using social media to promote brownie cakes. The implementation method starts from the preparation process which includes site survey activities and permits to carry out community service activities then prepare materials that will be given to partners. Meanwhile, the method of implementing the activities used consists of: Field Assistance, Integrated Training, Demonstration (practicum / applicative), Continuous Assistance. The target of this activity is the household industry of brownie cakes. The brownie cake business is known to be underdeveloped because business management is traditional, market segmentation is very limited, and it is not creative to utilize information technology in the form of social media for product marketing purposes. Social media that are widely used by the public today such as online stores, twitter, WhatsApp, line, Instagram, Facebook, and YouTube. These social media have not been optimally utilized for the purposes of promoting their merchandise products. The results of the activity show that partners have mastered the concepts of marketing, business management, and online promotion through social media.